Analysis of flavor characteristics of peanut porridge using gas chromatography-ion mobility spectrometry combined with intelligent sensory technology - Yuan, Bihua; Tian, Yun; Zhu, Xuan; Cheng, Kaiqi; Jin, Wengang; Liu, Qing; Li, Jing; Sun, Haiyan (Frontiers in Nutrition, 2025)
IntroductionThis study aimed to investigate the differences in flavor compounds between aged and fresh peanuts and their effects on peanut porridge aroma, taste, and volatile fingerprint profiles.MethodsGas chromatography–ion mobility spectrometry (GC-IMS), combined with electronic sensory technologies such as electronic tongue and electronic nose, was applied to analyze peanut porridge processed under different treatments. Partial least squares-discriminant analysis (PLS-DA) and principal component analysis (PCA) were used to identify characteristic volatiles and discriminate treatments.ResultsElectronic tongue and electronic nose analyses effectively distinguished peanut porridges based on flavor characteristics. A total of 47 volatile compounds were detected, including 10 alcohols, 10 esters, 6 ketones, 5 acids, 2 alkenes, 6 aldehydes, and 8 other compounds. PLS-DA identified 16 characteristic volatiles (VIP > 1), such as 2-pentanone, ethyl hexanoate, 2-acetylfuran, butanal, pentyl acetate, and heptanal. PCA showed that two principal components accounted for 66.7% of the total variance, enabling clear discrimination among treatments.DiscussionThe study systematically explored key differences in volatile compounds between aged and fresh peanuts and analyzed their impact on sensory attributes, particularly aroma and flavor perception. These findings enhance understanding of flavor formation mechanisms in peanut-based products and provide scientific evidence for flavor modulation, formulation optimization, product innovation, and quality control.